Perceptions of Female Administrative Employees on the New Career Advancement Model at Universidade Nacional Timor Lorosa'e - Ximenes, Fernanda Pires; Liestiawati, Fibria Indriati Dwi (Dinasti Research, 2024)
Female administrative employees at the Universidade Nacional Timor Lorosa'e (UNTL) have had the problem of decreasing the number of employees experiencing Career Advancement (CA) over the last three years. This shows that female employees have different needs with the new approach to the CA concept. Based on theory, Verma identifies new dimensions that expand the concept of CA through the lens of women's perception. The objective of this study is to test the dimensions of the new CA model, namely Future Aspiration (FA), Present Satisfaction (PS), and Career Orientation (CO) which are positively related to the career progress of female administrative employees at UNTL. A survey of female administrative employees was conducted and resulted in 140 respondents. Data were analyzed using univariate analysis and bivariate analysis using the Spearman correlation test. The results show that the three dimensions are positively related to the career progress of female administrative employees and CO has the strongest positive correlation of the three dimensions as shown in the correlation coefficient of 0.621 with a significance value of 0.000 (p<0.05).